Development of 21st Century Skills-Based Stereochemistry Learning Tools to Train Students' Argumentation Skills - Erika, Farah; Rahmadani, Agung (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to describe the validity of 21st century skills-based stereochemistry learning tools to train students' argumentation skills. This research is an educational design research with reference to the design of the Wademan development research model. The research instrument used was a learning tools validation sheet consisting of several validation sheets, namely: syllabus validation sheet, lesson plan validation sheet, teaching material validation sheet, student worksheet validation sheet, and argumentation skills assessment instrument validation sheet. The research data obtained from the validation and review sheets were analyzed descriptively and qualitatively. The expert's assessment of validation for each aspect of the assessment has good and very good validity criteria. These results indicate that learning tools that integrate the nature and complexity of the stereochemical structure of natural compounds from tropical rain forests can be used in the stereochemistry learning process.